Административное право России в вопросах и ответах: учеб. пособие / Н.М. Конин - Конин Николай Михайлович (Проспект, 2011)
Экземпляры: ф.2 (20101028) / Инвентарный номер: 96525 / Цена: 75 / Сис.шифр: 67.400я7 / Авт.знак: К 64 / ББК: 67.400я7